The popular policeman and other cases : psychological perspectives on legal evidence / Willem Albert Wagenaar, Hans Crombag. - Wagenaar, Willem Albert, 1941-; Crombag, H. F. M. (Henricus Florentine Maria), 1935- (Amsterdam University Press, 2005)
The role of psychologists, both in the courtroom and at the crime scene, is rapidly expanding. Surveying a wide range of international court cases, "The Popular Policeman and Other Cases " the critical - and often misunderstood - intersection of psychology and law. The authors, both expert psychologists with extensive experience in the courtroom, are quite familiar with the fundamental differences between the law and psychology as an empirical science. As well as dealing with well-known and controversial issues such as recovered memories or false confessions, "The Popular Policeman and Other Cases" examines a variety of less traditional criminal topics, including illegal gambling, trademark litigation, and the perils of risky courtship behavior. Each chapter reviews an actual case, appraises the relevant scientific research, and then demonstrates how psychological insights were introduced within the courtroom. The authors conclude by noting the outcome of each case - and how their research played a role in the decision. With its detailed investigation of the complex links between psychological research and its eventual application in the courtroom, "The Popular Policeman and Other Cases" fills a critical vacancy. It is virtually impossible for researchers to make significant progress within the field of law and psychology without experience as expert witnesses in actual trials. This casebook will be essential for their studies.